2009 IEEE Circuits and Systems International Conference on Testing and Diagnosis ICTD '09, Chengdu, China, April 28-29, 2009 / edited by Bing Long and Wenjiang Li. - Long, Bing; Li, Wenjiang (IEEE, 2009)
Testing and Fault Diagnosis for Digital, Analog and Mixed Circuits and Systems.